Building a sustainable clinical academic workforce to meet the future healthcare needs of Australia and New Zealand: report from the first summit meeting. Issue 9 (September 2015) - Windsor, J.; Searle, J.; Hanney, R.; Chapman, A.; Grigg, M.; Choong, P.; Mackay, A.; Smithers, B. M.; Churchill, J. A.; Carney, S.; Smith, J. A.; Wainer, Z.; et al.
Abstract The delivery of healthcare that meets the requirements for quality, safety and cost‐effectiveness relies on a well‐trained medical workforce, including clinical academics whose career includes a specific commitment to research, education and/or leadership. In 2011, the Medical Deans of Australia and New Zealand published a review on the clinical academic workforce and recommended the development of an integrated training pathway for clinical academics. A bi‐national Summit on Clinical Academic Training was recently convened to bring together all relevant stakeholders to determine how best to do this. An important part understood the lessons learnt from the UK experience after 10 years since the introduction of an integrated training pathway. The outcome of the summit was to endorse strongly the recommendations of the medical deans. A steering committee has been established to identify further stakeholders, solicit more information from stakeholder organisations, convene a follow‐up summit meeting in late 2015, recruit pilot host institutions and engage the government and future funders.